Deficit irrigation for improving the postharvest quality of lowland tomato fruits - Mohammed, H. N.; Tengku Muda Mohamed, Mahmud; Megat Wahab, Puteri Edaroyati (Universiti Putra Malaysia Press, 2018)
Arable lands are facing serious water scarcity due to climate change and available resources are depleting at an alarming rate which necessitate efficient use of water for agriculture. Deficit irrigation is an on farm strategy which is widely used in many crops to maximise crop productivity in drought prone areas. The present study was initiated to assess the effect of deficit irrigation at different growth stages of tomato (lycopersicon esculentum) on yield and fruit quality traits under greenhouse condition. Four regimes of irrigation: (T1) regular watering to field capacity (as control), (T2) irrigation every four days during vegetative stage, (T3) irrigation every four days throughout flowering stage and (T4) irrigation every four days during fruiting stage were evaluated in this study. The experiment was set up in a Randomized Complete Block Design (RCBD) with four replications. Data were collected from three fruit maturity stages: M3 (stage three, matured green), M4 (stage four, pink) and M6 (stage six, red) for yield, fruit weight, fruit number and the fruit quality parameters viz, firmness, soluble solids concentration, titratable acidity, pH, ascorbic acid and lycopene content. The results showed variable effects of deficit irrigation on most parameters studied. Soluble solids concentration were significantly increased under deficit irrigation at the flowering stage and increased from 5.25 brix (control) to 7.7 brix (fruiting) at stage three maturity index. The pH increased from 3.83 (control) to 3.97 (flowering) and 3.94 (fruiting) when fruits were harvested at stage three maturity index. In addition, the highest fruit firmness (3.4 N) was observed when fruit was harvested at stage three maturity under deficit irrigation (vegetative growth stage). Furthermore, lycopene content increased from 62.06 mg/kg in control plants to 67.91 mg/kg in plants which subjected to DI (vegetative) at stage six maturity index. However, water stress had no significant effect on titratable acidity, ascorbic acid and fruit weight. From the observations of this study, it can be concluded that T3 and T4 were adequately appropriate DI practices for MT1 tomato plants that could be recommended to tomato growers as deficit irrigation strategy for higher yield and quality.